Analisis Kritis dan Pragmatis Caring Economics sebagai Paradigma baru Kajian Ekonomi - Mit Witjaksono (Jurnal Ekonomi dan Studi Pembangunan, 2016)
This article critically and pragmatically analyze and expose the concept and basic principles of caring economics as a new paradigm of economics as opposed to neo-liberal economics and its implications to economic education in Indonesia. The analysis and exposition based on unobtrusive research techniques, i.e. comparative content analysis and historical notes among references used here and in the context of Pancasila and UUD 1945. The implications of the study in this article are formulated into three key recommendations: (a) the need to review and operational translation of Articles 33 and 34 of the UUD 1945 (Amendment IV, 2002); (b) the need to review the curriculum, learning approaches and tools, and practices of  learning economics in schools in order that caring economic becoming educational character of the national economy; and (c) the need to campaign of introduction to paradigm and practice of caring economics in the universities, both as an academic study or studies the development of teaching-learning models based on caring economics, through collaboration of higher education, school, community and local government.Keywords: caring economics, neo-liberal economics, pendidikan ekonomi,Pancasila, UUD 1945JEL Classification: B51, P51